2021
DOI: 10.21037/apm-21-1084
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous patient-controlled analgesia does not increase the risk of postoperative delirium compared to patient-controlled epidural analgesia: a propensity score-matched retrospective cohort study

Abstract: Background: It is unclear whether the doses of opioids and the routes of administration used for postoperative analgesic management are associated with delirium. We aimed to compare the incidence of postoperative delirium (POD) between intravenous patient-controlled analgesia (IVPCA) and patientcontrolled epidural analgesia (PCEA) in patients who underwent postoperative analgesic management using opioids.Methods: We retrospectively investigated surgical patients (n=3,324) who received patient-controlled analge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The PCIA infusion rate should be adjusted individually according to the needs of patients. The doses of dezocine and ketorolac tromethamine have not been classified hierarchically, and we still need to improve the research ( 24 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…The PCIA infusion rate should be adjusted individually according to the needs of patients. The doses of dezocine and ketorolac tromethamine have not been classified hierarchically, and we still need to improve the research ( 24 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering POD, a recent study did not find a difference in its incidence between morphine IV-PCA and fentanyl patient-controlled epidural analgesia (PCEA). After a propensity score matching patient characteristics, it was concluded that POD occurs regardless of the route and dose of opioid administration [43].…”
Section: Side Effects Of Iv-pcamentioning
confidence: 99%